PROCEDURAL ASPECTS OF EDUCATIONAL CHANGES: EMPIRICAL FINDINGS AT INSTITUTIONAL LEVEL - Semenets-Orlova, Inna (Advanced Education, 2017)
The researcher analyses special procedural aspects and important tools of organisational change management (at the level of higher educational establishments). As part of the study, the expert survey was conducted for the purpose of collecting empirical data for the analysis of practical experience of active participants of educational changes. The author surveyed 65 specialists from Ukraine who study the educational change issues in higher educational institutions in their professional or social activities. The survey was conditionally divided into several sections: general, procedural, resources provision of change, instrumental, analysis of change results, informative and analytical, expert evaluation of governmental educational change administration in Ukraine. The majority of questions concerned the determination of the required conditions for successful implementation of educational change. Based on the analysis of contemporary scientific literature, the author defined the logics and consistency of procedures of preparation for and immediate implementation of educational change. The omission of at least one of these procedures threatens the result of the overall process of educational changes. The author suggests that the low efficiency of educational change implementation in Ukrainian educational establishments is caused by neglect or improper use of essential preparation tools and procedures of proper educational change management support (underestimation of needs for sufficient resources, advisory support, awareness-raising campaigns, administration support, stimulation of participants and necessity of their continuous training).